2006
DOI: 10.1111/j.1746-6342.2006.00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori eradication prevents the development of gastric cancer – results of a long‐term retrospective study in Japan

Abstract: Summary Aim This large‐scale study was designed to investigate the incidence of gastric cancer after Helicobacter pylori (H. pylori) eradication in Japan. Methods This study was a retrospective multicentre study performed at 23 centres in Japan. Patients in whom H. pylori had been successfully eradicated and those in whom the infection persisted were entered into the study if they had undergone an upper endoscopic examination at least once a year for five consecutive years. The incidence rates of gastric cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…All patients had moderate or severe atrophy of the gastric mucosa, and 8 of 12 had intestinal metaplasia at baseline. In another multicenter study in Japan involving 3021 patients, gastric cancer developed in 23 (1%) of H. pylori-eradicated patients compared with 44 (4%) of those with persistent H. pylori infection, the period of follow-up being 7.7 years and 5.9 years for the eradicated and the noneradicated groups, respectively [63]. Another study on 1807 Japanese patients followed for approximately 3 years demonstrated a significant lower incidence of gastric cancer in patients whose infection was eradicated (6 of 1519) than in patients (5 of 288) with persistent H. pylori infection [64].…”
Section: H Pylori Eradication In Humans and The Risk Of Gastric Cancermentioning
confidence: 98%
“…All patients had moderate or severe atrophy of the gastric mucosa, and 8 of 12 had intestinal metaplasia at baseline. In another multicenter study in Japan involving 3021 patients, gastric cancer developed in 23 (1%) of H. pylori-eradicated patients compared with 44 (4%) of those with persistent H. pylori infection, the period of follow-up being 7.7 years and 5.9 years for the eradicated and the noneradicated groups, respectively [63]. Another study on 1807 Japanese patients followed for approximately 3 years demonstrated a significant lower incidence of gastric cancer in patients whose infection was eradicated (6 of 1519) than in patients (5 of 288) with persistent H. pylori infection [64].…”
Section: H Pylori Eradication In Humans and The Risk Of Gastric Cancermentioning
confidence: 98%
“…Our findings are consistent with the recent reports based on gastroendoscopical findings, which indicate lower gastric cancer rates in patients with a confirmed cure of H. pylori infection than in those who had not been treated or who had failed eradication therapy. [13][14][15][16][17]20,28 In all these studies, several years of follow-up were needed to confirm that successful eradication therapy significantly prevents the development gastric cancers. In the randomized, placebo-controlled, population-based study Wong et al 13 found during 7.5 years no gastric cancers after successful eradication therapy in 485 patients without premalignant lesions (atrophic gastritis, intestinal metaplasia or dysplasia) at baseline, but 6 cases appeared among 503 control patients (Kaplan-Meier analysis, log rank test, p ¼ 0.02).…”
Section: Epidemiologymentioning
confidence: 99%
“…In a retrospective Japanese multicenter study, gastric cancer developed within a median follow-up period of 5.9 years in 1% of 1,788 patients with eradicated infection compared with 4% of 1,244 patients with persisting infection within 7.7 years (OR, 0.36, CI: 0.22-0.62). 16 Takenaka et al 17 enrolled 1,807 patients to receive eradication therapy. At the latest follow-up endoscopy 12-118 months later, they recorded 6 cases of gastric cancers among 1,519 patients with a successful eradication of H. pylori, which was significantly less than the 5 cases found among 288 patients with failed eradication therapy 28 gave eradication therapy to patients hospitalised for peptic ulcer disease; 54,576 patients were treated early after the admission (median 14 days from it) and 25,679 patients at least a year later (median 1,053 days after the baseline admission).…”
Section: And Dementioning
confidence: 99%
See 1 more Smart Citation
“…65 Most data on the preventive effect of H. pylori eradication were generated in high incidence regions in Asia. A retrospective multicenter study from Japan analyzed the gastric cancer incidence in patients after H. pylori eradication for a 5-year follow-up in 23 centers including more than 3,000 patients [126]. Out of these, gastric cancer developed in 1% of patients who had been successfully eradicated and in 4% of patients with persistent infection (OR 0.36; 95% CI 0.22-0.62).…”
Section: Prevention Of Gastric Cancer-clinical Evidencementioning
confidence: 99%